ANALISIS GAYA KEPEMIMPINAN DI PT. SOLID UTAMA LOGISTIK SEMARANG - Sigit Agus Dwi Prasetyo (E-logis : Jurnal Ekonomi Logistik, 2021)
Leadership is very important in determining the goals to be achieved. Leaders of a company have their own leadership styles according to the personality and character of the leader himself. A leader has a very important role in a company. Leaders play a role in guiding and directing the company to achieve mutually determined goal. This research aims to determine the leadership style adoPT.ed by the leader of PT. Solid Utama Logistik Semarang. This research also aims to whether the leader has a role in the implementation of employee work and what are the role of the leader. The method used in this research is a qualitative research methods. In collecting data, this research uses observation, interview, and documentation methods. The results showed that leadership style applied by PT. Solid Utama Logistik Semarang was a participatory leadership style. The leader has a role as a leader, as a liaison, as a decision maker, as a spokesperson for the company, and the person who oversees and monitors employee performance.